THE CIVIL LAW EFFECTS OF A CONCORDAT MARRIAGE - Zabłocki, Jan (Zeszyty Prawnicze, 2018)
Marriage contracted under the provisions of canon law endows the newlyweds with a matrimonial bond which is indissoluble by its very nature; while the recognition of such marriages by the Polish State brings about the legal eﬀects envisaged under the country’s civil law. Thus, if a couple who married in church later divorce, the civil eﬀects of their marriage are terminated. In the event of an ecclesiastical annulment of the marriage its civil eﬀects continue in force, unless the couple are also granted a divorce in a court. Te determination of the or nullity of a marriage contracted under canon law rests entirely with the Church authorities.